1998
DOI: 10.1136/gut.43.5.612
|View full text |Cite
|
Sign up to set email alerts
|

First pass metabolism of ethanol is strikingly influenced by the speed of gastric emptying

Abstract: Background-Ethanol undergoes a first pass metabolism (FPM) in the stomach and liver. Gastric FPM of ethanol primarily depends on the activity of gastric alcohol dehydrogenase (ADH). In addition, the speed of gastric emptying (GE) may modulate both gastric and hepatic FPM of ethanol. Aims-To study the eVect of modulation of GE on FPM of ethanol in the stomach and liver. Methods-Sixteen volunteers (eight men and eight women) received ethanol (0.225 g/kg body weight) orally and intravenously, and the areas under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 40 publications
6
80
0
2
Order By: Relevance
“…Accordingly, it may be suggested that the less-thanadditive effects of the combined exposure to nicotine and ethanol described in the present study could be due to a reduction in ethanol plasma levels. However, this reduction was only described in animals that received oral ethanol, which led to the suggestion that it is related to a nicotineinduced delay in gastric emptying (Chen and Harle, 2005;Gilbertson and Barron, 2005;Nowak et al, 1987;Scott et al, 1993), causing an increased ethanol metabolization by the gastric alcohol dehydrogenase (Oneta et al, 1998). In fact, other studies indicated that chronic nicotine does not change ethanol concentration if ethanol is infused intravenously (Hisaoka and Levy, 1985).…”
Section: Methodsological Issuesmentioning
confidence: 99%
“…Accordingly, it may be suggested that the less-thanadditive effects of the combined exposure to nicotine and ethanol described in the present study could be due to a reduction in ethanol plasma levels. However, this reduction was only described in animals that received oral ethanol, which led to the suggestion that it is related to a nicotineinduced delay in gastric emptying (Chen and Harle, 2005;Gilbertson and Barron, 2005;Nowak et al, 1987;Scott et al, 1993), causing an increased ethanol metabolization by the gastric alcohol dehydrogenase (Oneta et al, 1998). In fact, other studies indicated that chronic nicotine does not change ethanol concentration if ethanol is infused intravenously (Hisaoka and Levy, 1985).…”
Section: Methodsological Issuesmentioning
confidence: 99%
“…Se determina, bien por la medida directa de la concentración de etanol en sangre o bien indirectamente por la medida de la tasa en el aire espirado 4,5 .…”
Section: Aspectos Socioeconómicosunclassified
“…Some of the alcohol which is ingested orally does not enter the systemic circulation but is oxidized mainly in the stomach (primary pathway involving gastric alcohol dehydrogenase enzymes) (Frezza et al, 1990), decreasing the bioavailability of alcohol (first pass metabolism) and thus BrAC. First pass metabolism of alcohol is modulated by many factors such as activity of gastric alcohol dehydrogenase enzymes (Frezza et al, 1990) and the speed of gastric emptying (Oneta et al, 1998). Delayed gastric emptying increases the time of exposure of alcohol to gastric alcohol dehydrogenase enzymes, increasing first pass metabolism of alcohol, leading to a lesser absorption and thus a lower BrAC.…”
Section: Alcohol Metabolism and Bracmentioning
confidence: 99%
“…Indeed, one way to circumvent legislation of selling hard liquors to underage people or in order to appeal to a younger generation (particularly young women) without the stigma of "hard liquor drinking, " is to propose pre-mixed, ready-to-use drinks combining distilled alcohol with added ingredients such as fruit juice, sugars and flavoring agents. Moreover, in those events, acute alcohol consumption in young people is often taken on a relatively empty stomach increasing the systemic availability of alcohol (Oneta et al, 1998).…”
Section: Introductionmentioning
confidence: 99%